2022
DOI: 10.3389/fnagi.2022.862856
|View full text |Cite
|
Sign up to set email alerts
|

Association of Endogenous Erythropoietin Levels and Iron Status With Cognitive Functioning in the General Population

Abstract: BackgroundEmerging data suggest that erythropoietin (EPO) promotes neural plasticity and that iron homeostasis is needed to maintain normal physiological brain function. Cognitive functioning could therefore be influenced by endogenous EPO levels and disturbances in iron status.ObjectiveTo determine whether endogenous EPO levels and disturbances in iron status are associated with alterations in cognitive functioning in the general population.Materials and MethodsCommunity-dwelling individuals from the Preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Consistent with our data, it has been shown that the expression of EPO and its receptor vary in different brain regions, and that the exogenous administration of EPO may contribute to improve oxidative metabolism and synaptic transmission capacities, in addition to produce improvements in various hippocampal‐dependent behavioral tests and short‐term spatial memory (Jacobs et al., 2021). Recent data suggest that higher endogenous EPO levels are associated with better scores on specific tests of cognitive functioning in the general human population (Ayerdem et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our data, it has been shown that the expression of EPO and its receptor vary in different brain regions, and that the exogenous administration of EPO may contribute to improve oxidative metabolism and synaptic transmission capacities, in addition to produce improvements in various hippocampal‐dependent behavioral tests and short‐term spatial memory (Jacobs et al., 2021). Recent data suggest that higher endogenous EPO levels are associated with better scores on specific tests of cognitive functioning in the general human population (Ayerdem et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This leads to increased oxygen consumption, which might activate the mechanisms that physiologically produce greater expression of EPO. EPO, together with other agents of neural plasticity, can also produce changes related to memory, although it has not been shown that this is directly due to hypoxia‐inducible factor 1 (Chin et al., 2000; Ayerdem et al., 2022). Spatial learning during the place recognition test can naturally generate a higher oxygen demand in activated neurons, which increases the expression of EPO and EPOr in a physiological way.…”
Section: Discussionmentioning
confidence: 99%